Theoretical Evaluation of Space Constants of Electrotronic Decay in Resistive Anisotropic Media: Common Equation - Veteikis, R. (Elektronika ir Elektrotechnika, 2008)
A mathematical model of the electrotonic potential distribution in a three-dimensional bidomain anisotropic resistive-capacitive medium (myocardium) is devised for the case when the source of current is point-, circle- disc- or cylinder-shaped. Using the superposition principle, the current electrode is approximated by point sources, arranging them on the perimeter of the circle-shaped electrode in two ways such that: a) the distances between them are identical in the metric system of coordinates; b) the distances between the point sources are identical in a normalized system of coordinates. The disk-shaped and cylinder-shaped current sources are approximated by point sources, evenly arranging them on the surface. Ill. 2, bibl. 23 (in English; summaries in English, Russian and Lithuanian).